2012
DOI: 10.1186/1749-799x-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Fixation method does not affect restoration of rotation center in hip replacements: A single-site retrospective study

Abstract: BackgroundAseptic loosening is one of the greatest problems in hip replacement surgery. The rotation center of the hip is believed to influence the longevity of fixation. The aim of this study was to compare the influence of cemented and cementless cup fixation techniques on the position of the center of rotation because cemented cup fixation requires the removal of more bone for solid fixation than the cementless technique.MethodsWe retrospectively compared pre- and post-operative positions of the hip rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Boudriot et al found that the intersection between Koehler's line (ilioischial line) and a line between the upper rims of the two obturator foramens (UOF) is a reliable landmark to determine the anatomic hip center [32]. Wegner et al used a line drawn through the top of the obturator foramen (UOF) to replace the IT line when the base of the teardrop was not clearly visible [33]. Our multiple measurements by different observers also demonstrate that the UOF exhibits accuracy no less than the IT line in both overall data and measurement results in the subdivided subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Boudriot et al found that the intersection between Koehler's line (ilioischial line) and a line between the upper rims of the two obturator foramens (UOF) is a reliable landmark to determine the anatomic hip center [32]. Wegner et al used a line drawn through the top of the obturator foramen (UOF) to replace the IT line when the base of the teardrop was not clearly visible [33]. Our multiple measurements by different observers also demonstrate that the UOF exhibits accuracy no less than the IT line in both overall data and measurement results in the subdivided subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we assumed that all cups were hemispherical in nature, although certain cup designs (e.g resurfacings) are not hemispherical or have a flattened pole area [32]. Fourthly, we only simulated impaction of an uncemented hemispherical cup rather than cemented components; however, Wegner et al [33] showed no difference in the ability to restore COR with different acetabular component fixation modes. Lastly, the present cohort comprised only patients with primary OA so the findings may not be applicable to patients with secondary OA hips.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reliability and agreement to evaluate measures in a longitudinal fashion was not studied. A relocation of COR by less than 5 mm in any direction horizontally or vertically has been described as optional by Wegner et al [19]. The same boundaries of 5-mm shortening or lengthening of the femoral offset have been described as the border defining short, normal, or increased femoral offset postoperatively after hip prosthesis [20,21].…”
Section: Discussionmentioning
confidence: 99%